Capacity Analysis of MIMO in Non-Uniform Nakagami Channel with Linear Receiver. Issue 6 (2nd November 2017) - Sur, Samarendra Nath; Bera, Rabindranath; Maji, Bansibadan
ABSTRACT: Multiple-input–multiple-output (MIMO) systems have emerged as a promising solution to provide high data rate wireless services in a rich scattering environment. This paper deals with the performance analysis of the MIMO system in correlated non-uniform phase distributed Nakagami-m channel with linear receiver. Authors have considered spatial diversity scheme i.e, vertical bell laboratories layered space-time (V-BLAST) systems in correlated MIMO Nakagami-m fading channels with equal power distribution among the transmitter side antennas. Also, they consider that the channel state information (CSI) is available only at the receiver. The paper presents a detailed analysis of the channel capacity in correlated and uncorrelated channel condition and validated the result with appropriate mathematical model. The effect of Doppler shift and Nakagami-m fading parameter m on the channel ergodic and outage capacity has been analyzed here.